The diagonal positioning of the goals modifies the external training load and the tactical behaviour of young football players - Canton, Albert (2021)
This study aimed to identify how positioning the goals in diagonal configurations on the pitch modifies the external training load and the tactical behaviour of young football players during small- sided games. Four teams of five outfield players and a goalkeeper played six small-sided games of five minutes’ duration in three different scenarios: 1) Control: goals placed one in front of the other; 2) Right diagonal goals: goals placed in the right-hand corner of the offensive half-pitch; and 3) Left diagonal goals: goals placed in the left-hand corner of the offensive half-pitch. The positioning-derived data from each player were collected with 10-Hz GPS units and were used to compute external load and tactical variables. Regarding the external load variables, differences were mainly focused on distance covered while walking in defence and game pace (variability), with higher values for the diagonal scenarios. Also, the length/width ratios in offence and defence were most likely lower in diagonal scenarios. In conclusion, the results showed that players’ adaptations to the environmental constraints of positioning the goals diagonally were the enhancement of the width team variable and the variability of the length.